Mylohyoid Nerve Injection for Unsuccessful Anesthesia of Posterior Teeth with Successful Inferior Alveolar Nerve Block. - Rozh M Hussein (Erbil Dental Journal)
Background and objective: variations in mylohyoid could lead to failure of an inferior alveolar nerve blockade. This study aimed to evaluate the impact of mylohyoid nerve variation on the persistence of pain following a successful inferior alveolar nerve block.